Evasão e permanência de discentes nos cursos de graduação presenciais do Centro de Ciências Exatas e da Natureza (CCEN/UFPB): um estudo de caso dos cursos de graduação em Matemática - Barbosa, Joseane de Pontes (2023)
The general objective of this dissertation is to understand how the permanence and evasion of students from undergraduate courses in mathematics at the Center for Exact and Nature Sciences (CCEN) is characterized, through a case study, analyzing characteristics of students, internal and external to the institution, in addition to the socioeconomic and political context surrounding dropout and permanence in higher education. The educational policies formulated in the 1990s were based on neoliberalism and globalization, prioritizing the private sector to the detriment of the public sector. From the Lula government (2003-2006/2007-2010), Brazilian public education was expanded and began to include a portion of the population historically excluded from this level of education, through programs such as the Support Program for Restructuring Plans and Expansion of Federal Higher Education Institutions (REUNI). It should be noted that despite the great importance of this movement, it included people in public higher education. Still, it has not guaranteed their permanence in undergraduate courses, since the data showed that the annual dropout rate in the country almost doubled between the years of 2006 and 2012, rising from 9.3% in the first year to 17.4% in the last year. This shows us the accentuated need to implement public policies directed to the permanence of students. We also stress that evasion is a multifaceted phenomenon that affects students, the institution, the educational system, and society in general. With regard to methodological aspects, the research carried out through this dissertation presents the following characteristics, regarding its approach: qualitative; for the scientific method: dialectic; its purpose: applied; and regarding its objectives: descriptive and exploratory. Among the survey results, we can highlight that most students come from public education; have low family income; 29.4% of freshmen said they were not in the desired course; they had reservations about the academic integration with the professors of the Department of Mathematics and the coordination of the course; indicated that the laboratories linked to the courses do not meet expectations; agree that participation in academic scholarship programs contributes to continuing education; indicate that the resources provided by the assistance programs contribute to continuing their studies.